Interleukin‐1 receptor antagonist promotes survival of ventral horn neurons and suppresses microglial activation in mouse spinal cord slice cultures. Issue 11 (26th June 2014) - Schizas, N.; Andersson, B.; Hilborn, J.; Hailer, N.P.
<x xml:space="preserve">Abstract</x> Secondary damage after spinal cord injury (SCI) induces neuronal demise through neurotoxicity and inflammation, and interleukin (IL)‐1β is a key inflammatory mediator. We hypothesized that IL‐1β is released in spinal cord slice cultures (SCSC) and aimed at preventing the potentially neurotoxic effects of IL‐1β by using interleukin‐1 receptor antagonist (IL1RA). We hypothesized that IL1RA treatment enhances neuronal survival and suppresses microglial activation. SCSC were cultured up to 8 days in vitro (DIV) in the presence of IL1RA or without, either combined with trophic support using neurotrophin (NT)‐3 or not. Four groups were studied: negative control, IL1RA, NT‐3, and IL1RA + NT‐3. IL‐1β concentrations in supernatants were measured by ELISA. SCSC were immunohistochemically stained for NeuN and α‐neurofilament, and microglial cells were visualized with isolectin B4. After 8 DIV, ventral horn neurons were significantly more numerous in the IL1RA, NT‐3, and IL1RA + NT‐3 groups compared with negative controls. Activated microglial cells were significantly less numerous in the IL1RA, NT‐3, and IL1RA + NT‐3 groups compared with negative controls. Axons expanded into the collagen matrix after treatment with IL1RA, NT‐3, or IL1RA + NT‐3, but not in negative controls. IL‐1β release from cultures peaked after 6 hr and was lowest in the IL1RA + NT‐3 group. We conclude that IL‐1β is released in traumatized spinal cord tissue and that IL1RA could exert its neuroprotective actions by blocking IL‐1‐receptors. IL1RA thereby sustains neuronal survival irrespective of the presence of additional trophic support. Microglial activation is suppressed in the presence of IL1RA, suggesting decreased inflammatory activity. IL1RA treatment approaches may have substantial impact following SCI. © 2014 Wiley Periodicals, Inc.